2002
DOI: 10.1144/gsl.sp.2002.193.01.14
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater quality in the Valigamam region of the Jaffna Peninsula, Sri Lanka

Abstract: The Valigamam region is underlain by a Miocene limestone formation and a highly porous soil cover. The region is totally dependent on groundwater to meet its agricultural, industrial and domestic needs, since other sources of water are seasonal. Recharge from rainfall is limited by high run-off and evapotranspirational losses. The region experiences water supply problems due to high concentrations of chloride, total hardness and nitrate in groundwater. The spatial distribution of chloride varies from year to y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 0 publications
3
25
1
Order By: Relevance
“…The HYDRUS-1D simulated potential groundwater recharge was 41.8 cm per year. This is 30-35 percent of the annual rainfall, in agreement with the estimates of Rajasooriyar et al (2002) for the study area. The recharge calculated by the WTF method based on measured groundwater levels was 29.8 cm.…”
Section: (Iv) Rechargesupporting
confidence: 88%
See 2 more Smart Citations
“…The HYDRUS-1D simulated potential groundwater recharge was 41.8 cm per year. This is 30-35 percent of the annual rainfall, in agreement with the estimates of Rajasooriyar et al (2002) for the study area. The recharge calculated by the WTF method based on measured groundwater levels was 29.8 cm.…”
Section: (Iv) Rechargesupporting
confidence: 88%
“…Year 2007 was a normal year with an annual rainfall of 1291 mm compared with other years, for example 2008, where the rainfall was higher than the average. The mean annual rainfall in the Jaffna Peninsula is approximately 1255 mm (Rajasooriyar et al, 2002). In the years 2008 and 2009 the annual rainfall was higher than in 2007.…”
Section: Soil Water Dynamicsmentioning
confidence: 93%
See 1 more Smart Citation
“…Continuing overdraft exceeding the safe yield may subsequently lead to progressive decline in groundwater table in the study area. This result had been supported earlier by Rajasooriyar et al (2002) where the groundwater level patterns for the period from 1979 to 1997 show differences in water level elevations by increasing the area of negative level elevations. Authors mentioned that excessive extraction of groundwater from wells, particularly from agricultural wells using highly efficient electrical pumps for prolonged periods, was the main course of the reduction in groundwater elevations.…”
Section: Annual Groundwater Balancesupporting
confidence: 70%
“…The estimation of annual water balance is critical for water management and development planning. Rajasooriyar et al (2002) reported that water shortage is a major problem and groundwater often serves as an important and safe source of water for the Jaffna Peninsula in Sri Lanka. The water resources of the basin remain almost constant while the demand for water continues to increase.…”
Section: Introductionmentioning
confidence: 99%